IMPLEMENTASI IMPORTANCE PERFORMANCE ANALYSIS (IPA) UNTUK MENGIDENTIFIKASI KEPUASAN MAHASISWA TERHADAP LAYANAN AKADEMIK - Ninik Zuroidah (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2015)
In this research, customer satisfaction index (CSI) use to know student satisfaction level of of academic services STAIN Kediri and importance performance analysis (IPA) to knowwhich attributes of services need to improve. Data collect with Quetioner. It’s used simple random sampling. Academic services that measuring areacademic advising, Campus Climate, Instructional Effectiveness), Registration Effectiveness, campus safety dan Security, Campus Support Service , Concern For the Individual, Recruitment and Financial Aid, Service Excellence, dan Student Centeredness.Validity and reliability test used determining attributes satisfaction level of academic services with Spearmen’s correlation and Cronbach Alpha coefficient. The respondents of this research is student of Education Departments. Results of this research are: 1) sudent satisfaction level of academic services is 57,72%. Suggestions for increasing customer satisfaction of academic services of STAIN Kediri are: 1) Support classes such as whiteboards, fan, LCD;2) Bathroom, toilet ; 3) Mosque; 4) Parks and public space area; 5) access wifi or internet hot spot for students; 6) staff faculty services with excellent.